Why Commodity Booms Have Not (Yet?) Boosted Human Capital: Bolivia’s Struggle to Create a Skilled Workforce - Fritz Brugger; Kathlen Lizárraga Zamora (Revue Internationale de Politique de Développement)
Do windfalls from the extractive sector help developing countries invest in human capital? To date, empirical studies remain inconclusive. Using Bolivia as a case study, this chapter examines the specific political-economic dynamics that led the country to increase spending on education yet at the same time failed to build a skilled workforce. Overall, the study finds that while the mining sector continued to seek unskilled, cheap labour, the capital-intensive hydrocarbon sector, for its part, developed on-the-job training programmes. Meanwhile, education policies failed to anticipate evolving demand from the labour market. As a result, vocational training suffered, a situation further compounded by efforts of powerful groups in the education sector to protect their own, somewhat narrow interests, at the expense of educational achievements. It concludes that the rise of private education and popular skills-based training programmes cannot substitute for development of a functional vocational training system, capable of supporting the country’s ambition to develop a world-class lithium processing industry with linkages in strategic sectors.